2016
DOI: 10.1002/term.2119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative facile methods for preparing graphene oxide-hydroxyapatite for bone tissue engineering

Abstract: Motivated by the success of using graphene oxide (GO) as a nanofiller of composites, there is a drive to search for this new kind of carbon material as a bioactive component in ceramic materials. In the present study, biomineralized GO was prepared by two different approaches, represented by in situ sol-gel synthesis and biomimetic treatment. It was found that in the biocomposites obtained by the sol-gel approach, the spindle-like hydroxyapatite nanoparticles, with a diameter of ca. 5 ± 0.37 nm and a length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 51 publications
1
55
0
2
Order By: Relevance
“…Especially for Synthesis C, this is almost completely absent even in composites that have a greater amount of GO. This is probably due to the loss of the crystallographic order after ultrasonication and to a greater intercalation of the nano HAp particles between the graphenic planes (Li et al, ; Raucci et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for Synthesis C, this is almost completely absent even in composites that have a greater amount of GO. This is probably due to the loss of the crystallographic order after ultrasonication and to a greater intercalation of the nano HAp particles between the graphenic planes (Li et al, ; Raucci et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the GO–HAp composites, HAp is strongly and uniformly intercalated with the GO sheets that act as a nucleation site. Compared with the HAp, the prepared GO–HAp nanocomposites displayed an increased solubility in water with higher GO percentages due probably to the lower crystallinity of HAp composites with intercalated GO sheets (Raucci et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting functions of GO among all its merits is that it can promote hydroxyapatite (HAP) mineralization due to its polar groups . In some HAP‐containing composite materials, the presence of GO improved the bioactivity and also induced an osteogenic differentiation through osteoblast phenotype of Human Mesenchymal Stem Cells (hMSCs) . This makes GO suitable for utilization in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In some HAP-containing composite materials, the presence of GO improved the bioactivity and also induced an osteogenic differentiation through osteoblast phenotype of Human Mesenchymal Stem Cells (hMSCs). [32] This makes GO suitable for utilization in bone tissue engineering. By incorporating GO, scaffolds with improved osteogenic bioactivity can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…) demonstrated that the HA particles were in a typical spindle‐like shape with a diameter of about 5.0 ± 0.4 nm and a length of around 20.0 ± 2.5 nm. These sizes are smaller than hydroxyapatite nanoparticles obtained by the same process and reported in our previous work . This effect may be because, these nanoparticles (B_HA 10 , B_HA 20 ) are oriented with their c ‐axis parallel to the gelatin axis and showed a smaller sizes due to the presence of gelatin that probably reduces the crystals growth …”
Section: Resultsmentioning
confidence: 41%